P250 Correlation between Attendance Rates and Socioeconomic Deprivation at a Difficult Asthma Clinic in a Large Inner City Teaching Hospital. (12th November 2015) - Dillon, C; Mault, S; McDonough, B; Ahmad, M; Narang, Y; Burhan, H; Beveridge, NER
Abstract : Introduction and objectives: Missed clinic appointments are a huge financial burden on the NHS, with an average of 6.9 million outpatient appointments being missed each year. 1 The difficult asthma clinic at our inner city hospital is no exception to this trend. Many factors are likely to contribute to missed appointments, which can be summarised in with in socioeconomic deprivation indices. We wanted to confirm whether there is an association between missed appointments and socio-economic deprivation. We hypothesised that non-attenders lived in areas with worse deprivation scores. Method: We compared deprivation scores of English postcodes of clinic attenders and non-attenders of a 'difficult asthma clinic' between 2011–2014 inclusive. Indices of multiple deprivation scores were using census related data and Townsend Index via UK data service ©University of Essex and University of Manchester. This provides a validated, relative measure of deprivation across small localities in England to enable comparison. A higher score represents an area with worse socio-economic deprivation, maximum score = 100. Mann-Whitney two-tailed tests to compare non-paired non-parametric data were performed in Prism version 6 (GraphPad). Results: The median deprivation score of postcodes of non-attenders (n = 458) was 60.69, whereas for attenders it was 51.12 (n = 505), with a p value of <0.0001. Conclusion: These results strongly suggest socioeconomic deprivation has a negative impact on attendance rates at this specific clinic. Challenging socio-economic conditions are detrimental to healthcare in multiple ways and it can be difficult for patients to access resources needed to manage their healthcare need effectively. However, we hope to assess the effect of deprivation in a control medical clinic to explore the specificity of this result to asthma clinics. It would also be valuable to investigate if these DNA rates are reflected in community clinics, as this may be an alternative way to deliver this service in order to reduce overall DNA rates in deprived areas. Reference: 1 http://www.england.nhs.uk/2014/03/05/missed-appts/